Visualization of Carotid Doppler in Patients with Ischemic Stroke at Dr. Hasan Sadikin General Hospital Bandung Year 2016-2019 - Olivia Olivia; Ahmad Rizal Ganiem; Syarief Hidayat (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Various pathological changes in both the intra and extracranial arteries that supply the brain can cause disturbance of cerebral blood flow and perfusion leading to cerebral dysfunction. Doppler ultrasound is able to assess these changes. This study was performed to evaluate the anatomical and physiological changes found in the carotid arteries of patients with ischemic stroke using Doppler ultrasound.Methods: The cross-sectional descriptive study design with total sampling method was conducted on the medical records of ischemic stroke patients who had carotid Doppler ultrasound at the Department of Cardiology and Vascular Medicine Dr. Hasan Sadikin General Hospital Bandung from 2016 to 2019. Demographic data, such as stroke diagnoses and plaque characteristics recorded in the Doppler reports were collected.Results: There were 38 data sets collected. The distribution and characteristics of atherosclerotic plaques were similar between the two carotid systems, with the same percentage of plaque being found in the right (31.6%) and left (36.8%) carotid system. The most common type of plaque found was type III and was located in the common carotid artery. Thrombus was absent in all patients. Intimal media thickening was found in 13.2% right system and 15.8% left system. Stenosis was present in 34.2% of patients, and most had <50% stenosis. Peak systolic velocity increased (>125 cm/s) in 5.3% of the right system and 7.9% of the left system of the internal carotid artery.Conclusions: Most of the atherothrombotic and thromboembolic type of ischemic stroke patients in this study have normal carotid Doppler ultrasound features. Further study on the presence of plaque in ischemic stroke patients in Indonesia is needed.